Governance Arrangements for IT Project Portfolio Management Qualitative Insights and a Quantitative Modeling Approach - Frey, Thorsten; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Due to the growing importance of IT-based innovations, contemporary firms face an excessive number of proposals for IT projects. As typically only a fraction of these projects can be implemented with the given capacity, IT project portfolio management as a relatively new discipline has received growing attention in research and practice in recent years. Thorsten Frey demonstrates how companies are struggling to find the right balance between local autonomy and central overview about all projects in the organization. In this context, impacts of different contextual factors on the design of governance arrangements for IT project portfolio management are demonstrated. Moreover, consequences of the use of different organizational designs are analyzed. The author presents insights from a qualitative empirical study as well as a simulative approach. Contents IT Project Portfolio Management IT Governance Business IT/Alignment Centralization and Decentralization Target Groups Information management and project management researchers and students IT project portfolio management and IT governance practitioners The Author Dr. Thorsten Frey received his doctorate at the chair of Information Systems / Software Business & Information Management at the Technische Universität Darmstadt, Germany. His areas of interest are Information Management, IT Governance, and Project Portfolio Management.
IT Project Portfolio Management -- IT Governance -- Business IT/Alignment -- Centralization and Decentralization.
Keywords: Business; Corporate governance; Organization; Planning; Information technology; Business -- Data processing; Business and Management; Organization; IT in Business; Corporate Governance; Electronic books